(3JLQHI aj JOQjH eYdej GdQjGVjGJ(B: (3GdJZjQ aj JUhQGJ GdeYdejf Mhd Md GdeSGFd h aj eeGQSGGJge GdJYdjejIs - (3OGZQ, GfWhGfs ((3HjQhJs (3cdjI GdJQHjI aj GdLGeYI GddHfGfjI(B- (3HjQhJs, 2004)
(3GUHM Mqd GdeSGFd Yf GdeLGdGJ PGJ GdChdhjI aj JYdje GdQjGVjGJ Ydi GdUYjO GdYGdej efP GdYGe (B1980 (3JbQjHkG(B. (3hbO GhdJ efGgL GdQjGVjGJ aj dHfGf (B(1997) (3CgeqjI NGdUI HgPG GdeLGd(B. (3hHSHH GdehbY Gdege dMd GdeSGFd aj JYdje GdQjGVjGJ hGdi UYhHGJ GdJdGejP aj Md GdeSGFd hUYhHGJ GdeYdejf aj JYdjeg GROGO GdGgJeGe HGYOGO eYdej GdQjGVjGJ hJOQjHge Ydi JYdje Md GdeSGFd(B. (3haj SjGb JOQjH eYdej GdQjGVjGJ ddUa GdMGOj YTQ bGe GdHGMK HGLQGA JLQHI JOQjH Jbhe Ydi Md GdeSGFd GYJeGOG Ydi fehPL (B"(3GdOQS GdfehPLj(B" (3GdebQQ QSejkG HYO JYOjdg dLYdg GcKQ GfSLGeG eY adSaI GdefGgL GdLOjOI(B. (3cGf GdgOa ef GdOQGSI GdJYQa Ydi JUhQGJ GdeJOQHjf Mhd Md GdeSGFd aj eeGQSGJge GdJOQjHjI hYdi GdJZjQ aj gPg GdJUhQGJ hGdeeGQSI aj GSJNOGege dMd GdeSGFd aj GdJYdje(B. (3abO GXgQJ OQGSGJ YOjOI JCUjQ JUhQGJ GdeYdejf Mhd GdQjGVjGJ hYdi eeGQSGJge GdJYdjejI(B. (3hbO bUO GdHGMK HJUhQGJ GdeYde Mhd GdQjGVjGJ GdGMcGe GdTNUjI hGdBQGA hGdXfhf hGdeYJbOGJ GdeJYdbI HWHjYI GdQjGVjGJ hJYdegG hJYdjegG(B. (3MGhdJ GdJLQHI GdJYQa Ydi BQGA GdeYdejf aj GdJOQjS bHd GdJOQjH hHYOg, hGYJeOJ JOQjHkG jbhe Ydi Mqd GdeSGFd, hJVef efGbTGJ hGfTWI Mhd Md GdeSGFd aj GdJYdje(B. (3SeMJ GdJLQHI HGdJYQa Ydi HYV JUhQGJ GdeJOQHjf heeGQSGJge GdJYdjejI GdeJYdbI HGSJNOGe Md GdeSGFd aj GdJYdje(B. (3ceG HjfJ GdJLQHI Cf GdJOQjH SGYO GdeJOQHjf Ydi age GaVd ddefGgL GdLOjOI ddQjGVjGJ aj dHfGf hdWQGFb JYdjegG(B. (3ceG HjfJ hLhO JUhQjf eNJdajf Mhd Md GdeSGFd geG(B: (3GdJUhQ (B"(3GdJYdej GdGLQGFj(B" (3Gj GecGfjI GSJNOGe Md GdeSGFd HgOa JYdje GdGLQGAGJ, hGdJUhQ (B"(3GdJYdej Gdeaghej(B" (3Gj GecGfjI GSJNOGe Md GdeSGFd HgOa JYdje GdeaGgje(B.s
(3GdfhY (B: (3ebGds
Keywords: Formation continue des enseignants; L$1 (Benseignement du Mathss; Math education; Teachers in-service training; (3JOQjH GdeYdejfs; (3JYdje GdQjGVjGJs